Sustainability integration in EFL curricula: Evidence from Indonesian and Malaysian Universities - Jarjani Usman; Astri Yulia; Abd Razak Zakaria; Safrul Muluk; Kemal Kurnia Hasan; Jana Safira Jarjani (Universitas Syiah Kuala, 2025)
This study investigates the integration of the 17 Sustainable Development Goals (SDGs) in English as a Foreign Language (EFL) curricula within Indonesian and Malaysian universities. Specifically, it examines how SDGs are represented in EFL curricula, how EFL lecturers perceive the integration of SDGs, and how they implement SDG-related content in their teaching practices. Drawing on Bronfenbrenners (2000) Ecological Systems Theory (EST), a qualitative narrative inquiry was employed, using document analysis of course outlines, lecture slides, and materials, and assessments, as well as semi-structured interviews with nine EFL lecturers from four universities. Course documents were analyzed using content analysis to examine SDG integration in the curricula, while interview transcripts were thematically analyzed, coded, and mapped onto ESTs microsystem and mesosystem levels. The content analysis of syllabi and course materials showed limited and inconsistent references to SDGs, with few explicit outcomes, activities, or assessments. Microsystem analysis showed all nine lecturers valued integrating SDGs in EFL to build students knowledge, skills, and attitudes; whereas, mesosystem data indicated the SDG implementation was driven mainly by individual initiative, with only sporadic program- or campus-level support. The nine lecturers also reported a mix of course-embedded activities and co-/campus initiatives to integrate SDGs. To move beyond ad hoc efforts, universities should embed the SDGs in learning programs and learning outcomes, provide SDG-ready materials and assessment rubrics, fund professional development, and offer rewards and incentives for supporting consistent integration.